Effects of oral meal feeding on whole body protein breakdown and protein synthesis in cachectic pancreatic cancer patients. Issue 3 (20th April 2015) - van Dijk, David P.J.; van de Poll, Marcel C.G.; Moses, Alastair G.W.; Preston, Thomas; Olde Damink, Steven W.M.; Rensen, Sander S.; Deutz, Nicolaas E.P.; Soeters, Peter B.; Ross, James A.; Fearon, Kenneth C.H.; Dejong, Cornelis H.C.
Abstract: Background: Pancreatic cancer is often accompanied by cachexia, a syndrome of severe weight loss and muscle wasting. A suboptimal response to nutritional support may further aggravate cachexia, yet the influence of nutrition on protein kinetics in cachectic patients is poorly understood. Methods: Eight cachectic pancreatic cancer patients and seven control patients received a primed continuous intravenous infusion ofl ‐[ring‐ 2 H5 ]phenylalanine andl ‐[3, 3‐ 2 H2 ]tyrosine for 8 h and ingested sips of water withl ‐[1‐ 13 C]phenylalanine every 30 min. After 4 h, oral feeding was started. Whole body protein breakdown, protein synthesis, and net protein balance were calculated. Results are given as median with interquartile range. Results: Baseline protein breakdown and protein synthesis were higher in cachectic patients compared with the controls (breakdown: 67.1 (48.1–79.6) vs. 45.8 (42.6–46.3) µmol/kg lean body mass/h, P  = 0.049; and synthesis: 63.0 (44.3–75.6) vs. 41.8 (37.6–42.5) µmol/kg lean body mass/h, P  = 0.021). During feeding, protein breakdown decreased significantly to 45.5 (26.9–51.1) µmol/kg lean body mass/h ( P  = 0.012) in the cachexia group and to 33.7 (17.4–37.1) µmol/kg lean body mass/h ( P  = 0.018) in the control group. Protein synthesis was not affected by feeding in cachectic patients: 58.4 (46.5–76.1) µmol/kg lean body mass/h, but was stimulated in controls: 47.9 (41.8–56.7) µmol/kg lean body mass/h ( P  = 0.018). Both groups showed a comparable positive net protein balance during feeding: cachexia: 19.7 (13.1–23.7) and control: 16.3 (13.6–25.4) µmol/kg lean body mass/h ( P  = 0.908). Conclusion: Cachectic pancreatic cancer patients have a higher basal protein turnover. Both cachectic patients and controls show a comparable protein anabolism during feeding, albeit through a different pattern of protein kinetics. In cachectic patients, this is primarily related to reduced protein breakdown, whereas in controls, both protein breakdown and protein synthesis alterations are involved.